RISK MANAGEMENT, BOARD CONTROL AND EARNINGS QUALITY OF LISTED NON-FINANCIAL FIRMS IN NIGERIA - Abba, Hirhyel Ibrahim; Fali, Ibrahim Mallam; Kauji, Mohammed Bukar; Ampong, Kwabena (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The study investigates the moderating impact of board control on the relationship between risk management and earnings quality of non-financial firms listed on the Nigeria exchange group from 2013 to 2022. 43 listed non-financial firms in Nigeria form the sample size. Ex-post facto research design, earnings quality was the dependent variable, risk management as the independent variable while board control is the moderating variable. The findings of study indicate that board control significantly moderate impact of board risk management committee, risk appetite and audit committee significantly improve earnings quality. However, the study found that the interaction of board control and risk culture weakened the influence of risk culture in mitigating earnings management. The study concluded that board risk management committee, risk appetite, audit committee, and board control are necessary yardstick for improving the quality of reported earnings. The study therefore, recommends that shareholders of listed non-financial firms in Nigeria should pay more attention in appointment of board of directors, since board control substantially aid risk management in mitigating earnings manipulations. The results contribute to corporate governance and risk management debates in an emerging economy such as Nigeria and have policy implications on regulators and shareholders in refining the effectiveness of the risk management policies.